FUNDAMENTALISME RADIKAL DALAM PEMIKIRAN DAN GERAKAN POLITIK KEAGAMAAN DI INDONESIA: STUDI KASUS PEMBUBARAN HIZBUT TAHRIR INDONESIA (HTI) - Kisno Hadi; May Linda Sari (Institut Filsafat dan Teknologi Kreatif Ledalero, 2021)
This article describes on radical fundamentalism group named Hizbut Tahrir Indonesia (HTI). Fundamentalism is a concept, an idea that lives in political thought and religious political movement which is recognized blooming out in Indonesia as a side product of reformation era in 1998. Because of its ideology was consider as an opposite to Indonesian ideology and law, HTI then disbandment by Indonesian government. This article is a library research that uses a descriptive qualitative method. There are three Research results i.e., firstly, radical fundamentalism is a thought and a religious-political movement of a group that strictly carries out religious teachings. And these concepts exist in all religions. Secondly, although activities and political movements of HTI were stopped by government, its concept and movement are still running by many other religious group. And thirdly, the thought and political movement of HTI and other religious fundamentalist groups needs to be criticized to add insight into ideology.Key words: Radical Fundamentalism, Hizbut Tahrir Indonesia, Religious Thought and Political Movement.